A Comparative Study to Assess the Awareness and Utilization of Maternal Health Services Provided Under the Pradhan Mantri Matru Vandana Yojana among the Antenatal Women in Urban and Rural Areas in the State of Maharashtra - Shivaji Banate, Anita (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of this study was to assess the awareness and utilization of maternal health services provided under the Pradhan Mantri Matru Vandana Yojana (PMMVY) among antenatal women in urban and rural areas of Maharashtra. Research Methodology: This community-based study was conducted in selected urban and rural communities in Maharashtra, with a total of 300 antenatal women selected through simple random sampling. Data were collected using a semi-structured questionnaire and self-reported checklist. Descriptive and inferential statistics were used to analyze the data. Results: The study found that 50.67% of antenatal women in urban areas and 46.67% in rural areas had good awareness regarding the PMMVY. In addition, 26.67% of women in urban areas and 38% in rural areas had average awareness, while 18% of urban women and 5.33% of rural women demonstrated excellent awareness. However, 4.67% of urban women and 10% of rural women showed poor knowledge regarding the scheme. Conclusion: The findings indicate that antenatal women exhibit inadequate awareness and utilization of PMMVY. To improve awareness and utilization, there is a need for health programs, public education, and strengthening of primary healthcare services. These measures will enhance maternal and child health and contribute to the reduction of maternal and child mortality.